Kedudukan Keanggotaan Dewan Perwakilan Daerah Dalam Sistem Ketatanegaraan - Utamy, Hebby Rahmatul; Efendi, Roni (Universitas Muhammadiyah Sumatera Barat, 2019)
The Regional Representative Council (DPD) as a new institution formed based on the amendments to the 1945 Constitution places the DPD as a state institution that accommodates and fights for the rights of the region and regional representatives in the context of the government system in Indonesia. DPD membership is chosen based on the General Election with one of the provisions that DPD members must be independent as stipulated in Article 182 letter l of Law Number 7 of 2017 concerning ELECTION that there are other work phrases interpreted as constitutionally paid as work that also doubles as an administrator or functionary of a political party, because it can lead to a conflict of interest with the duties, authority, and rights as DPD members in accordance with statutory provisions. This is intended so that the DPD can work without any intervention from any party. However, the legal facts that occur in the current state administration system are found in many DPD members who also double as administrators of political parties. In juridical normative this is clearly constitutional, if viewed from a different perspective with reference to the Supreme Court decision, concurrent positions are not contrary to the constitution because this relates to the constitutional rights of citizens to work in any sector.